1980
DOI: 10.1002/cjce.5450580411
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and interfacial physical properties of aqueous solutions of sodium lauryl sulphate: Part IV: Dilute aqueous solution behavior by electron spin resonance studies and by pH and surface tension measurements

Abstract: The electron spin resonance spectrum of the nitroxide label 2,2,6,6 – TetraMethyl – 4 – Piperidone – Oxide (TEMPO) has been investigated in aqueous solutions of a purified and commercially available impure samples of sodium lauryl sulphate (NaLS) for a wide range of concentrations. The spectra were recorded at 24°C as a function of surfactant concentration. The reorientational correlation times Tθ of the TEMPO label in aqueous solutions were calculated using the Kivelson's theory. Using the Tθ data qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…They evidenced some premicellar changes in the correlation times of a spin probe, 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO). These results are in agreement with ref , revealing premicellar association in sodium dodecyl sulfate (SDS) solutions.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…They evidenced some premicellar changes in the correlation times of a spin probe, 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO). These results are in agreement with ref , revealing premicellar association in sodium dodecyl sulfate (SDS) solutions.…”
supporting
confidence: 93%
“…Using four different types of spin probes in their experiments and after extensive analysis of the data, they have suggested that the observed aggregation processes cannot be attributed to any probe-induced effect. A rather detailed study of the probe correlation time in a wide premicellar concentration range was reported in a paper . The authors have suggested the formation of micellar type of aggregates.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations